READ WRITE EASY Research, practice and innovation in deaf multiliteracies (Volume 1) - Webster, Jenny; Zeshan, Ulrike (Ishara Research Series, 2021)
" This book is the first of two volumes on deaf multiliteracies based on research with deaf children and adults in India, Uganda and Ghana. Multiliteracies include not only reading and writing but also skills in sign language, drawing, acting, digitally mediated communication, and other modes. The book covers a variety of themes including the assessment of learners' progress, pedagogical issues as seen from teachers' perspectives, and issues related to curricula. Authors discuss, for instance, the use of multimedia portfolios for tracking the learning of deaf primary school children, the training needs of deaf teachers, and a collaborative approach to curriculum development. The book is of interest to both researchers and practitioners. In addition to four research chapters, it features four 'innovation sketches'. These are reports of innovative practices that have arisen in the context of the research, and they are particularly relevant for practitioners with an interest in methodologies."